Coordination chemistry of gold with N-phosphine oxide-substituted imidazolylidenes (POxIms). (28th October 2019) - Branzi, Lorenzo; Baron, Marco; Armelao, Lidia; Rancan, Marzio; Sgarbossa, Paolo; Graiff, Claudia; Pöthig, Alexander; Biffis, Andrea
Abstract : Diverse gold complexes are found to be accessible with the title ligands, which exhibit peculiar structural features and promising catalytic performances. Abstract : N -Phosphine oxide-substituted imidazolylidenes (POxIms) have been employed as heteroditopic ligands towards gold centres. Both bis-carbene and mono-carbene gold(i ) complexes have been obtained, depending on the steric bulk of the employed POxIm ligand. Oxidation of the gold(i ) complexes with halogens or halogen synthons allows access to both bis-carbene and mono-carbene gold(iii ) complexes, depending on the nature of the starting gold(i ) complex and on the oxidation conditions. In all these complexes, the phosphanyl oxide moiety of the ligand is found to not be coordinated by the gold centre, although the crystallographic and spectroscopic characterization of the compounds suggests in most cases the existence of weak electrostatic interactions. A preliminary screening of the complexes as precatalysts in the intermolecular hydroamination of phenylacetylene with mesitylamine has also been carried out.